Experience and perception of family members on child's hospitalization in pediatric unit - Tayane Próspero Cardoso; Pâmela Roberta de Oliveira; Rosa Jacinto Volpato; Vagner Ferreira do Nascimento; Elias Marcelino da Rocha; Alisséia Guimarães Lemes (Universidade Federal de Santa Maria, 2019)
Aim: to identify the perceptions experienced by accompanying relatives of children during hospitalization. Method: exploratory, qualitative research carried out in a pediatric sector in the interior of Mato Grosso from May to June 2015. Data was obtained through semi-structured interviews with the relatives of hospitalized children and submitted to thematic analysis. Results: the mothers were more present as companions during the hospitalization and, in some cases, were the first contact with the pediatrics sector. The physical structure was considered satisfactory. Some of the feelings and attitudes expressed were despair, fear, impotence/helplessness, longing, and hope. Final considerations: the study pointed out the need for reception of family members by the entire health team during the hospitalization of the child, while including them in the treatment process, attending to their physical and psychological needs, and thus contributing to an improvement in the quality of childcare